Contrasting realities: corporate environmental disclosure and stakeholder‐released information. Issue 1 (2014) - ,
Abstract : Purpose – This paper aims to study the informational dynamics that take place between a firm and its stakeholders with respect to corporate environmental management.Design/methodology/approach – The analysis is based on a case study contrasting environmental information reported by the case firm with environmental information about the firm disclosed by four stakeholder groups or their representatives (governments, the community, environmental non‐governmental organizations and investors) over three years. The information flow of disclosure is also considered.Findings – The results suggest that the informational dynamics are composed of multiple related patterns. The patterns range from correspondence between disclosures to stakeholders complementing or contradicting corporate disclosures. Different patterns are associated with different levels of interactions from stakeholders, who are most involved when they combine disclosure patterns around key environmental issues for the forest industry. Limited interactions are observed from the firm, suggesting a symbolic engagement within the dynamics and a strategic accountability approach.Research limitations/implications – Limitations are found in the focus on disclosure outlets without examination of their production and reception, and in the inherent nature of the documents collected to represent each perspective. Some stakeholder groups were excluded from the study due to data unavailability.Originality/value – This paper offers an in‐depth analysis of firm‐stakeholders interactions with respect to environmental reporting and maps the information flow of their disclosure. Acknowledgements : This study constitutes a significant part of the author's PhD dissertation accomplished at Concordia University (Montréal, Canada). As such, she would like to thank her dissertation chair, Michel Magnan, and her dissertation committee members, Emilio Boulianne, Charles Cho and Denis Cormier, for their helpful guidance and comments in the development of this project. The author is also grateful for the helpful comments and suggestions provided by Marcia Anissette, Nola Burh, Salvador Carmona, Christopher Chapman, Yves Gendron, Jean‐François Henri, Matias Laine, Mélanie Roussy, Ikäheimo Seppo, Crawford Spence and Helen Tregidga on earlier versions of this paper. Comments and suggestions from participants of the 2008 CSEAR Summer School, the 2009 European Accounting Association Conference, the 2009 Emerging Scholars Colloquium of the Interdisciplinary Perspectives on Accounting Conference and the 2010 Asian Pacific Interdisciplinary Research on Accounting Conference were also appreciated. Last but not least, the author is also in debt to the two anonymous reviewers who were of tremendous assistance in developing the paper. The financial support of the Social Sciences and Humanities Research Council of Canada, the Ordre des Comptables Agréés du Québec and Université Laval is gratefully acknowledged.